Elementary statistics - Blay, Basilia Ebora (Anvil Pub., 2007)
"Elementary Statistics is a useful compendium of instructional modules and worksheets that introduces learners to the rudiments and applications of statistics in research. It goes beyond descriptive statistics (or the mere summarizing and describing of facts and figures) and delves thoroughly into the realm of statistical inference enabling novice researchers to formulate and test hypotheses, make predictions and decisions, and draw conclusions based on the results of statistically-analyzed data."--Back cover.